A comprehensive review on passive design approaches in green building rating tools. (October 2015) - Chen, Xi; Yang, Hongxing; Lu, Lin
Abstract: Buildings are the major consumers of energy in Hong Kong and most urban areas in the world. Building environmental assessment schemes, and green building rating tools (GBRTs) have been adopted by architects, engineers and researchers for more than 20 years to help promote more sustainable construction activities. Each rating tool highlights energy use as a significant portion of the assessment and provides guidance on more energy efficient strategies. Building energy efficiency can usually be improved by both passive and active technologies. Active design involves making more energy efficient heating, ventilation, air-conditioning (HVAC) systems, hot water production, lighting and any other building services application, whereas passive design focuses more on building envelope related aspects determined by the architectural design so as to reduce the demand of the building for energy. Recently, there has been renewed interest in passive strategies because of the low extra investment and the potential benefits in energy saving. The passive design approach has also been recognized in the latest versions of green building rating tools. Five representative rating systems, which all developed their own passive design criteria leading to the award of credits, are subject to comparative examinations in respect of the comprehensiveness, effectiveness and accuracy of each criterion in this paper. Passive design criteria including the building layout, envelope thermophysics, building geometry, air-tightness and infiltration performance and their effects on building energy consumption are also comprehensively reviewed. The results show that a holistic design approach based on passive energy saving strategies proves to be an effective way to reduce building energy budgets. However, more consolidated weighting systems to enable comparison of different passive strategies should be incorporated in green building rating tools based on further sensitivity and parametric studies.